The potential of Moringa oleifera seeds for fungal disinfection in water - Siti Nur Syazana, Zakaria; Che Ku Mohammad Faizal, Che Ku Yahya; Noor Yahida, Yahya (Elsevier Ltd, 2022)
Water contamination by fungi has earned more attention by numerous researchers, while disinfection is one of the primary methods used in drinking water treatment process to remove bacteria or fungi. In this work, a pilot study on the characterization and the performance of the regrowth fungal spores on Moringa oleifera (MO) disinfection process were investigated. Firstly, an active compound in MO seeds was extracted and characterized via Fourier-transform infrared (FTIR) and scanning electron microscopy (SEM) analyses. The extract MO then underwent a comparison set of disinfection studies without any disinfectant at different time to evaluate its performance in reducing the growth of fungal spores in water. The disinfection study reveals that fungi's spore’s growth decreased from 71% to 60% from day two until day seven. In addition, these findings indicate that extract MO seeds may be a potential disinfectant for the growth of fungi in drinking water.